(untitled) (The Macau Ricci Institute Journal, 2020)
For the last century or so, the defining economic paradigm of modern nations has been that of ‘the Consumer Society’ (Baudrillard 1970). The phrase describes a set of dynamics in which users of products and services are identified as consumers who follow the acquisitive tendency to maximise the benefits of their consumption. By so doing they ensure the maintenance of economic progress and the provision of benefits to consumers and also to wider society, through the redistribution of surplus value.